Live Stream Shopping: The Influence of Personal Values and Emotional Pleasure on Millennials’ Purchase Intention - Barida Rakhma Nuranti; Ayu Diana Ansori; Reska Anggara Putra (Universitas KH. Abdul Chalim Mojokerto, 2026)
Live-shopping, or shopping via live-streaming, has emerged as a global trend in the online shopping setting. Marketers are increasingly leveraging live-streaming features on social media platforms to engage audiences and enhance interaction during online shopping. The interactiveness, convenience, and seamless nature of live-shopping often trigger emotional responses among consumers, which may stem from the fulfillment of personal values throughout the live-shopping session. Nevertheless, the extent to which personal values and emotional pleasure influence consumer purchase intention remains underexplored. This study employs a quantitative approach through a survey method. The data were analyzed using SEM-PLS. Based on responses from 200 live-shopping consumers, this study reveals that personal values, consisting of hedonic values and utilitarian values, positively influence emotional pleasure and shopping intentions. Furthermore, emotional pleasure positively influences shopping intentions.